A Study to Evaluate the Analgesic Efficacy of Transdermal Diclofenac Sodium Patch in Minor Oral and Maxillofacial Procedure - Pratikshya Kothai; Santosh Kumar Subudhi; Sthitaprajna Lenka; Subrat Kumar Padhiary; Satchidananda Meher (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aims and Objectives: The aim and objectives of this study are to evaluate and determine the efficacy oftransdermal diclofenac patch in control of pain following Routine Extractions, Transalveolar extractions,Soft tissue biopsies, to evaluate any adverse reactions following the usage of the transdermal patch and torelate its efficacy to the gender, pre-surgical condition of the patient and time taken for the procedure.Materials and methods: A clinical study was done in the patients coming to the Oral and Maxillofacialsurgery department, Institute of Dental Sciences, SOA University. A total of 537 patients were selected fromour patients in Oral and Maxillofacial Surgery department who underwent routine extractions, Transalveolarextractions, Soft tissue biopsies etc.Results: 500 patients who underwent minor surgical procedures under local anaesthesia with adrenaline.The patient has then prescribed a diclofenac patch for analgesic purpose and the efficacy and tolerability ofthe patch was evaluated. Using SPSS software, statistical analysis was done. All the patients were evaluatedwith VAS scale and Wong baker scale on 1st day, 2nd day and 3rd day. The mean age of the patient is 28.2years and the mean value for the time taken for the procedure is 14.4 min.Conclusion: Transdermal patch can be effectively used for analgesic effect following minor oral surgicalprocedures of lesser duration. It is effective for the management of mild to moderate pain relief as it hasproved to be a good option as an analgesic especially in patients with gastric problems and for bettercompliance.